Pengurangan Ketidakpastian pada Pekerja Salon Tunarungu dalam Melayani Pelanggan Baru - Andheka Malestha; Ratri Kusumaningtyas (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2020)
This research aims to know how the forms of uncertainty experienced by deaf salon workers, as well as how they reduce uncertainty in communicating with new customers. This research is a qualitative descriptive research, such as for the collections of data using in-depth interviews and observations of 4 people at the deaf salon workers. The research of this studi show the form of uncertainty experienced by the workers among others: 1) Cognitive uncertainty, worries about the limitations they have made them difficult to get clear information, not able to understand customer’s wishes, fear will get bad prejudice from customers. 2) Behavior uncertainty is an inability to estimate new customer behavior, worry there will be complaints if you are not satisfied with the treatment provided, worries about a customer bidding a lower price than the one set. The process of reducing uncertainty experienced by deaf salon workers: 1) Proactive process, where the deaf salon workers thinks about the communication options it will do, they great them directly, think of verbal communication and not. 2) Retroactive process, where the deaf workers explained how to interact with new customers, how the attitude and behaviors of the opponent talk about interacting with them. In addition to the uncertainty reduction strategy undertaken by deaf salon workers. 1) Passive strategy, by doing observations as an effort to find out about new customers and what do they have to do. 2) Active strategy, deaf salon workers looking for information using third person help or in other words ask about someone through others. 3) Interactive strategy, deaf salon workers perform interactions directly to reduce the sense of uncertainty they experience.